Micropropagation of Sentang (Azadirachta Excelsa (Jack) Jacobs) - Jainol, Juddy E. (1997)
The large-scale propagation of sentang CA. excelsa (Jack) Jacobs) through seeds is impractical as the seeds are recalcitrant and they loose viability in a short period Therefore this study sought to develop a protocol for the micropropagation of sentang. It involved the determination of an appropriate sterilization technique, a suitable explant to be used, appropriate medium and plant growth regulators for shoot formation, multiplication and rooting, as well as estimating the rate of multiplication. Means of solving problems of defoliation during rooting and shoot elongation were also developed. A comparative study on the rootability of shoots excised from the initial culture and final subculture was also conducted.